Systemic determination of infrastructure criticality. (1st January 2013) - Katina, Polinpapilinho F.; Hester, Patrick T.
The aim of critical infrastructure (CI) research efforts is to develop strategies to protect infrastructure systems by reducing hazards, risks, and threats from natural and manmade events. Given that no nation has unlimited resources, the current trend is to prioritise infrastructures so that the most 'critical' infrastructure systems are given priority in terms of resources. An extensive literature review reveals that current approaches to assessing infrastructure criticality may not be generalisable and transportable because they are aimed at specific sectors or regions. Hence, the purpose of this paper is to propose an initial set of 'criticality' factors to enable CI prioritisation regardless of sector or region. To achieve this purpose, this paper is organised into four primary areas. First, the authors provide background information on the need for holistic CI 'criticality' factors to enable prioritisation. Second, the authors conduct a literature review on current approaches to prioritisation and their limitations. Third, the authors introduce a generalisable four-tuple of criticality factors fundamental for infrastructure prioritisation. The paper concludes with challenges and areas suggested by the authors for future research.